Analysis of Scientific Literacy of Senior High School Students in Relation to Global Warming as a Socio-Scientific Issue - Hernani, Hernani; Depi, Siska Sintia; Hidayat, Lina Nurlina; Nurhadi, Atep Rian; Supriatna, Asep; Tias, Bachrul; Wafi, Wulanda (JEC, 2024)
The low scientific literacy skills of Indonesian students should be a serious concern for all science educators. Scientific literacy skills can be improved in contextual learning related to nature and social contexts that occur in the environment around students. This study aims to develop the science literacy of high school students through the application of Problem Based Learning model on the topic of global warming. This study used a quantitative approach with descriptive methods, with participants of 24 students in one of the high schools in Bandung City.  The research instrument used is a science literacy test question in the form of descriptions, which consists of 3 domains, namely context, content, and science competence, in addition, student handouts is also used to provide an overview of the PBL learning process containing the applied science literacy.  The result shows students performed Moderately in three PISA-based competencies including (i) explaining scientific phenomena, (ii) evaluating and designing scientific investigations, and (iii) analyzing evidence and data scientifically for decision-making and action.